(3JMdjd GdeMJhi aj HMhK GdEYdGe (B/s - (3YHO GdMejO, eMeOs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 2010)
(3jUOQ gPG GdcJGH ceMGhdI eJhGVYI dJdHjI MGLI GdecJHI GdYQHjI hGdHGMKjf Edi Odjd efgLj dGSJNOGe JMdjd GdeMJhi aj HMhK GdEYdGe, hjbOe EWGQkG ehMOkG ddfXQjI hGdJWHjb, jYhV GdfbU GdedehS aj gPG GdeLGd, hGYJeO efgL GdcJGH Ydi eSM JQGK JMdjd GdeMJhi GdfXQj hGdJWHjbj aj GdOQGSGJ GdZQHjI hGdYQHjI djbOe OQGSI efgLjI ehMOI JQcR Ydi GdNWhGJ GdELQGFjI ddefgL hGSJNOGeGJg aj HMhK GdEYdGe ef NdGd GdfXQI GdYdejI ddHMhK hGdOQGSGJ GdYQHjI GdJj JfGhdJg Ch GSJNOeJg cefgL dJMbjb GdXGgQI GdJj JJfGhd eMJhi GdEYdGe HGdHMK hGdOQGSI(B. (3haj MOhO GdgOa GdYGe dgPG GdcJGH GdPj jSYi Edi JbOje Odjd efgLj eJcGed ddEWGQ GdfXQj dJMdjd GdeMJhi hcjajI GSJNOGeg hJWHjbg aj HMhK GdEYdGe, bSeJ GdOQGSI Edi SJI aUhd, jgJe GdGhd hGdKGfj efgG HGdEWGQGdfXQj hGdefgLj, hJbOe GdaUhd GdCQHYI GdJGdjI GdEWGQ GdJWHjbj GdPj jJfGhd MOhO GdNWhGJ GdefgLjI hCSS GSJNOGegG, hGdJWHjbGJ GdYedjI dgG aj GdHMhK hGdOQGSGJ GdefThQI aj JMdjd GdeMJhi hPdc cGdBJj(B:- (3GdaUd GdChd(B: (3JYQja JMdjd GdeMJhi hJGQjNg, GdaUd GdKGfj(B: (3GdEWGQ GdefgLj dJMdjd GdeMJhi, GdaUd GdKGdK(B: (3GdNWhGJ GdefgLjI GdYGeI, GdaUd GdQGHY(B: (3JQejR HjGfGJ GdJMdjd, GdaUd GdNGeS(B: (3GdYO hGdbjGS, GdaUd GdSGOS(B: (3GdJMdjd aj GdOQGSGJ GdcjajI, GdaUd GdSGHY(B: (3JMdjd eMJhi GdehGbY GdEYdGejI, GdaUd GdKGef(B: (3JaSjQ GdfJGFL(B. s
Keywords: (3GdHMhKs; (3GdEYdGes